Improving Digital Branding of Kranggan Tourism Village - Reza Anggriyashati Adara (Warmadewa Press, 2024)
Digital branding can increase the chances of a tourist attraction becoming known to the public. This event was conducted to provide basic knowledge of digital branding to the stakeholders of tourism village in Kranggan, Bekasi. This research aimed to enhance the digital branding strategies of Kranggan Tourism Village in Bekasi by providing stakeholders with essential knowledge and practical examples. The event was attended by 20 participants. They consisted of civil servants, public citizens and various elements of public who were hoping to improve the quality of tourism village of Kranggan. This event consisted of two stages. The first stage was an introduction of the importance of digital branding toward a tourist attraction. The second stage was a presentation from a content creator about the examples of digital branding conducted by one of clothing brands. This event distributed a survey to monitor the participants' opinions regarding the event.